Agency in the face of path dependence: how organizations can regain scope for maneuver - Johann Fortwengel; Arne Keller (Business Research, 2020)
This paper tackles a key problem in path dependence research: how can locked-in organizations regain their scope for maneuver? Leveraging insights from two surprising and thus revelatory cases of organizations that have successfully escaped from path dependence, we develop the theoretical argument that regaining scope for maneuver can be achieved by interrupting the logic of a path's underlying self-reinforcing mechanisms. More specifically, we argue that, through a targeted interruption of the working of these mechanisms, hyper-stable patterns inscribed in an organization can be gradually rewound-and alternative futures become possible. We position our paper within larger debates around the role of agency in path dependence theorizing, and we outline research frontiers to better understand the necessary antecedents of and exact relationship between mechanisms interruption and pattern unwinding.
Keywords: 650; Path dependence; Self-reinforcing mechanisms; Lock-in Agency